Surgical hernia of the abdominal right inferior quadrant. - Croci, Fabio; Gastambide, Carmelo; Terra, Eneas; Cordal, Adriana (Cirugía del Uruguay, 1984)
The authors present a series of 36 surgical hernia of the abdominal right inferior quadrant, a secondary ef• fect of appendicectomy incisions. Studied are its clinical, anatomopathological, therapeutic and evolutiva aspects. Special mention is made of the frequency of the necessity of using prosthesic material for the resolution of same.